2012
DOI: 10.1063/1.3675993
|View full text |Cite
|
Sign up to set email alerts
|

Development of a miniature fan motor

Abstract: A novel compact axial flux fan motor was developed. Such a micromotor could be a potential candidate for using as the cooling solution for the next generation mobile devices, for example, smart phones and pico-projectors. The key parameters of the motor, such as back electromotive force, cogging torque, and axial preload are predicted using finite element method. In addition, new approaches are proposed to measure these items, and the corresponding experimental results are in good agreement with the simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…E ngines are systems that convert different kinds of energy into mechanical motion, which are used in various microscale systems, including laboratory-on-a-chip microreactors (1-3), microelectromechanical (MEMS) actuators (4), and microscale heat exchangers (5,6), to name just a few. Some of the most important members of the engine family are liquid pumps.…”
mentioning
confidence: 99%
“…E ngines are systems that convert different kinds of energy into mechanical motion, which are used in various microscale systems, including laboratory-on-a-chip microreactors (1-3), microelectromechanical (MEMS) actuators (4), and microscale heat exchangers (5,6), to name just a few. Some of the most important members of the engine family are liquid pumps.…”
mentioning
confidence: 99%
“…Wang et al [171] identified that based on the consumer preferences for miniature and multifunctional products, more and more portable electronics field, such as small-form-factor information storage devices, personal digital assistants, smart phones, Pico projectors, and so forth, have been driven in our daily life to make our information and communication sharing faster and easier.…”
Section: Miniature Fluid Dynamic Bearingmentioning
confidence: 99%